American biodiversity in Lamiinae (Coleoptera, Cerambycidae): description of three new species of Eupogonius LeConte and new distribution records - Bezark, Larry G.; Santos-Silva, Antonio (Zootaxa, 2023)
Three new species of Eupogonius LeConte, 1852 (Desmiphorini) are described from Mexico: E. rifkindi sp. nov., from Colima and E. martinezi sp. nov. and E. pulcher sp. nov., from Nayarit. A new country record is provided for Eupogonius piperitus (Bates, 1885) and new country (Belize) and state (Mexico, Oaxaca) records are provided for Drycothaea spreta Bates, 1885 (Calliini). The differences between D. spreta and D. turrialbae (Breuning, 1943) are discussed. Additional new distribution records are presented for Canidia ochreostictica (Dillon, 1956) and Stenolis multimacula Monné, 2011 (Acanthocinini). In a recent paper by us, the repository acronyms listed under materials and methods do not match the repository acronym listed for the new species, the type repository for those four new species is clarified herein.